Rainbows amid Downpours: University Students’ Goals in Learning English during Digital Experiments - Toquero, Cathy Mae Dabi; Acebes, Swen Joshryll C.; Melitante , Jaizele B.; Tuble, Nikki T. (REiLA : Journal of Research and Innovation in Language, 2021)
University students are susceptible to the constantly shifting online milieu during the pandemic. Linguistic isolation can present more difficulties as students lack authentic social communication in classes online. This study examined the hopes and goals of university students in their English learning course during emergency remote learning. Third Year Pre-Service teachers of a state university in the Philippines served as participants in this study. Through content analysis of 28 student-responses of the English Modules, the research findings demonstrate the significance of hopes and goals of the university students in learning English during the pandemic. Amidst the digital experiments, students portray hopes and goals of developing their pedagogical skills in English and broadening their linguistic skills despite linguistic isolation. Students' goals in the course are to improve their language skills, develop in-depth knowledge in English, achieve better grades, and become effective potential teachers. As they aim to achieve those goals amid metaphorical downpours, university students reflect on the purpose of the course to equip them for lifelong learning that may develop ethical value, morality, and sense of vocation in their chosen profession. Despite having to confront the difficulties of learning online, their hopes and aspirations spark a burning desire to engage in intellectual and linguistic battles in learning English during pandemic and post-pandemic. Academic implications include for teachers to integrate authentic assessments for experiential language learning and for students to sketch a visual career plan outlining how students may achieve their goals as future educators.